2010
DOI: 10.1080/00423110903337273
|View full text |Cite
|
Sign up to set email alerts
|

A structural articulation method for assessing railway bridges subject to dynamic impact loading from track irregularities

Abstract: This paper discusses the importance of track irregularities in railway bridge design, and presents a new technique for calculating the dynamic impact load induced by such irregularities: the structural articulation method. The properties of the combined bridge-suspension system are coupled through global mass, stiffness, and damping matrices. Under the proposed method, the true suspension system over a particular point on the bridge girder at time t is divided into equivalent suspension systems attributed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to the literature, the LAF is influenced by several track and rolling stock parameters including, but not limited to, wheel flatness 17,18 , the train's un-sprung mass 19,20 , surface imperfections of the rail 14,15 , the conditions of the sleeper support 21,22 , the mechanical properties of the rail pad 23 , nonlinear behaviour of the track 24 , and the stiffness of the track. 25 The research reported in this paper sought to develop mathematical models for the correlation between the above track and rolling stock parameters and the track's design criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the LAF is influenced by several track and rolling stock parameters including, but not limited to, wheel flatness 17,18 , the train's un-sprung mass 19,20 , surface imperfections of the rail 14,15 , the conditions of the sleeper support 21,22 , the mechanical properties of the rail pad 23 , nonlinear behaviour of the track 24 , and the stiffness of the track. 25 The research reported in this paper sought to develop mathematical models for the correlation between the above track and rolling stock parameters and the track's design criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Railway bridge design is also an area where serious studies have been made on the effects of dynamic impacts due to loads. [14][15][16] Despite recent developments in the comprehension of the dynamic nature of train loads and their impact on the structure of tracks, there remains potential for further investigations. In particular, the simultaneous application of a wider range of track and rolling stock parameters could be considered in tandem with all the design criteria of the track's components.…”
Section: Introductionmentioning
confidence: 99%